Dentinal Microcrack Formation after Root Canal Instrumentation by XP-Endo Shaper and ProTaper Universal: A Microcomputed Tomography Evaluation - Sarah M. Alkahtany; Ebtissam M. Al-Madi (Hindawi Limited, 2020)
Aim. To evaluate dentinal microcrack formation on root canals instrumented, continuously in the body temperature, with XP-endo shaper (XPES) and ProTaper Universal (PTU), by means of microcomputed tomographic (micro-CT) analysis. Methodology. Nineteen mesial roots with two separate canals (Vertucci Type IV) of extracted mandibular molars were used in this study. The root canals (N = 38) were divided into 2 groups. Group 1 (n = 19): all MB canals were instrumented with XPES. Group 2 (n = 19): all ML canals were instrumented with PTU. All roots were scanned with micro-CT before and after instrumentation. Two precalibrated examiners evaluated the cross-sectional images of each sample with DataViewer program. The dentinal microcracks (complete and incomplete) were counted in each third of the root for the preinstrumentation and the postinstrumentation images. Wilcoxin signed-rank and Mann-Whitney U tests were used for statistical analysis at a significance level of P<0.05. Results. The number of microcracks increased significantly (P<0.05) after instrumentation with XPES in the middle and cervical thirds. The number of microcracks increased significantly (P<0.05) after instrumentation with PTU in the cervical third only. There was no significant difference between the groups in the cervical and apical thirds. In the middle third, the XPES induced more incomplete microcracks than PTU (P<0.05). Conclusion. Within the limitations of this study, there was no significant difference in the dentinal microcrack formation between XPES and PTU in the apical and cervical thirds of the root. However, XPES instrumentation induced more incomplete microcracks than PTU in the middle third of human roots.